RESPONSE OF MUSKMELON CULTIVARS TO PLASTIC MULCH AND IRRIGATION REGIMES UNDER GREENHOUSE CONDITIONS - M. Alenazi; H. Abdel-Razzak; A. Ibrahim; M. Wahb-Allah; A. Alsadon (Journal of Animal and Plant Sciences, 2015)
Mulching and irrigation water management is among the vital practices that are being applied in commercial vegetable production. White-on-black plastic mulch in combination with four irrigation levels (40, 60, 80 and 100% based on crop evapotranspiration (ETc)) was applied to assess growth and yield responses of two F1 muskmelon cultivars (‘Velta’ and ‘Parana’) under greenhouse conditions. Crop water productivity (water use efficiency, WUE and irrigation water use efficiency, IWUE) were also evaluated. Plastic mulch treatment resulted in higher plant height, leaf area, fruit number, early fruit yield, total yield and crop water productivity than non-mulch treatment. High and medium irrigation levels (100 and 80% ETc) enhanced plant height and leaf area and increased fruit number, early and total yield. On the other hand, low irrigation levels (40 and 60% ETc) decreased yield and increased WUE and IWUE. ‘Velta’ plants showed superior vegetative growth, higher crop yield, WUE and IWUE than ‘Parana’ plants. A higher crop production was observed with mulch and 100% ETc treatment for ‘Velta’ cultivar. However, higher WUE and IWUE values were found under mulch with the lowest irrigation level (40% ETc) for ‘Velta’ cultivar. Plastic mulch with 80% ETc water treatment was considered more suitable for optimizing WUE with no major yield reduction. For muskmelon yield enhancement with 20% saving in irrigation water, it is recommended to apply medium irrigation level (80% ETc) and plastic mulch under greenhouse conditions.
Keywords: Muskmelon; white-on-black plastic mulch; crop yield; crop water productivity